2021
DOI: 10.3390/ijms22094946
|View full text |Cite
|
Sign up to set email alerts
|

EGCG-Mediated Potential Inhibition of Biofilm Development and Quorum Sensing in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa (P. aeruginosa), one of the dangerous multidrug resistance pathogens, orchestrates virulence factors production through quorum sensing (QS). Since the exploration of QS inhibitors, targeting virulence to circumvent bacterial pathogenesis without causing significant growth inhibition is a promising approach to treat P. aeruginosa infections. The present study has evaluated the anti-QS and anti-infective activity of epigallocatechin-3-gallate (EGCG), a bioactive ingredient of the tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 73 publications
2
20
0
Order By: Relevance
“…EGCG exerted an inhibitory effect on the formation of amyloids through aggregating FapC monomers into oligomers [ 99 ]. EGCG inhibited the development of biofilm formed by Pseudomonas aeruginosa and reduced the elastase activity, swimming and swarming motility [ 100 ]. The biofilm formed by Staphylococcus aureus V329 was disassembled by EGCG [ 101 ].…”
Section: Mechanisms Underlying the Beneficial Effects Of Egcg On Skin Wound Healingmentioning
confidence: 99%
“…EGCG exerted an inhibitory effect on the formation of amyloids through aggregating FapC monomers into oligomers [ 99 ]. EGCG inhibited the development of biofilm formed by Pseudomonas aeruginosa and reduced the elastase activity, swimming and swarming motility [ 100 ]. The biofilm formed by Staphylococcus aureus V329 was disassembled by EGCG [ 101 ].…”
Section: Mechanisms Underlying the Beneficial Effects Of Egcg On Skin Wound Healingmentioning
confidence: 99%
“…Furthermore, novel treatments may be used alone or in combination with conventional therapies, such as the inhibition of QS and bacterial lectins, the use of iron chelation, phage therapy, vaccine strategies, as well as the use of nanoparticles, antimicrobial peptides and electrochemical scaffolds ( Chatterjee et al, 2016 ). In our previous study, the minimal inhibitory concentration (MIC) of EGCG against P. aeruginosa was confirmed to be 512 ÎŒg/ml ( Hao et al, 2021 ). However, EGCG reduced virulence phenotypes, such as biofilm, protease, elastase activity, swimming, and swarming motility at concentrations where no growth inhibition was observed.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies have demonstrated the diverse activities of Epigallocatechin-3-gallate (EGCG), including antioxidant, antibacterial, antiviral, antitumor and anti-inflammatory activities. In our previous study, we demonstrated that EGCG significantly acted against the expression of P. aeruginosa QS-regulated virulence in vitro , and significantly increased the survival rate of Caenorhabditis elegans infected with P. aeruginosa ( Hao et al, 2021 ). QS quenching, called anti-virulence therapy, has been considered a suitable strategy to settle the multidrug resistance problem ( Clatworthy et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural products targeted specific genes that inhibit the growth or pathogenicity of bacteria and control extracellular virulence, such as EGCG, Curcumin, and Eugenol-Containing Essential Oils, which have been investigated as QS inhibitors ( 23 – 25 ). Paeonol is a polyphenolic compound originally extracted from Paeonia lactiflora , Moutan cortex , and Cynanchum paniculatum , which has been used wildly due to various medicinal benefits as an analgesic, antipyretic, and anti-inflammatory agent in traditional Chinese medicine ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%